Is there a correlation between the aggressiveness of chronic asymptomatic prostatitis National Institutes of Health category IV and the Gleason score in patients with prostate cancer? - Aglamis, Erdogan; Ceylan, Cavit; Akin, Mehmet Mustafa (Canadian Urological Association, 2020)
Introduction: We evaluated the correlation between the International Society of Urological Pathology (ISUP) grades and the aggressiveness grades of prostate inflammation in newly diagnosed prostate cancer patients with chronic asymptomatic prostatitis National Institiutes of Health (NIH) category IV (CAPNIHIV). Methods: The study comprised 357 consecutive patients with prostate cancer in whom a cancer diagnosis had been made via a prostate needle biopsy. Histological sections of the prostate biopsy specimens of the patients were reviewed and scored. Prostatic inflammation was scored using the aggressiveness grade of inflammation. The associations between the ISUP grades and the aggressiveness grades of inflammation were analyzed using logistic regression. The limi tations of the study were its retrospective design and the limited number of cases. Results: In 110 (31%) patients, CAPNIHIV was detected: 56 (51%) patients had a grade 0 aggressiveness score, 34 (31%) patients had a grade 1 aggressiveness score, and 20 (18%) patients had a grade 2 aggressiveness score. The patients who had prostatic inflammation had 1.65 times (95% confidence interval [CU 1.05-2.61) greater likelihood of a high ISUP grade (grade >= 3) compared with the patients who did not have prostatic inflammation. The association between the ISUP grade and the aggressiveness grade of inflammation was more pronounced for a grade 2 aggressiveness score (n= 20; odds ratio 2.97; 95% CI 1.14-7.71). Conclusions: In prostate cancer patients with CAPNIHIV, there was a positive correlation between the inflammation aggressiveness grade and the ISUP grade. The aggressiveness of intraprostatic inflammation may be an important morphological factor affecting the Gleason score.
Keywords: Chronic Inflammation; Antigen Levels; Intraepithelial Neoplasia; International Society; Risk; Men; Hyperplasia; Infection; Tissue